Chemical Fingerprinting of Tussilago farfara by RP-HPLC and Hierarchical Clustering Analysis - Li, Chang-Tian; Yan, Zheng-Fei; Tian, Feng-Hua; Mao, Xin-Xin; Li, Yu (Asian Journal of Chemistry, 2014)
The aim of this study was to establish a method for extraction and chemically fingerprinting of extracts of Tussilago farfara and to apply this method to 12 T. farfara samples collected from different regions in China. RP-HPLC with gradient elution was performed on rutin. Comparing with the chromatograms, it showed that the samples were divided into two groups. Thirteen characteristic peaks were found in the extracts of all samples. Peak at retention time of 17.45 min was identified as rutin. Hierarchical clustering analysis showed the similar results as the visual comparison. The RP-HPLC method allowed it simple to identify and compare T. farfara. This was the first report on hierarchical clustering analysis of T. farfara.